Cognitive poetics : goals, gains and gaps - Brône, Geert, 1978-; Vandaele, Jeroen (Mouton de Gruyter, 2009)
For more than two decades now, cognitive science has been making overtures to literature and literary studies. Only recently, however, cognitive linguistics and poetics seem to be moving towards a more serious and reciprocal type of interdisciplinarity. In coupling cognitive linguistics and poetics, cognitive poeticians aim to offer cognitive readings of literary texts and formulate specific hypotheses concerning the relationship between aesthetic meaning effects and patterns in the cognitive construal and processing of literary texts. One of the basic assumptions of the endeavour is that some.
Keywords: Cognitive grammar.; Poetics.; Literature -- Philosophy.; Grammaire cognitive.; Poétique.; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax.; Literature -- Philosophy; Cognitive grammar; Poetics; Cognitive linguistics.; textlinguistics.; Electronic book.